(untitled) (Confluenţe Bibliologice, 2024)
The relevance of addressing the issue of occupational stress is driven by its prevalence in the social environment and its negative consequences for staff and organizations. The article provides insights into the factors causing discomfort in librarians’ work. It proposes methods for preventing stress and mitigating its effects.